Problem Keilmuan Kontemporer dan Pengaruhnya Terhadap Dunia Pendidikan - Mohammad Muslih (TSAQAFAH, 2012)
This articledeparts from the assumption that education is actually a scientific activity ,in a sense related to theimplementation,development and dissemination of knowledge. However, in education, study of knowledge and it’ s relation with the educational process remains a neglected area. In the perspective of philosophy of science, contemporary issue to this is the issue of the nature of science and the growth of science. Relation to education, a growing problem then is how the consequences of building science to education. If education means the process of promoting and developing human knowledge, how should the process be done? This article asserts that the concept and praxis of education proved to havea relationship with the scientific problem. Criticism of the nature of science is certainly going to be able to  clarify the pedagogical logic of educational praxis. Theory and methodolog y of education has become a pretty interesting studyin pedagogy. While “educational paradigm” is a philosophical discussion in Philosophy of Education, Sociology and History of Education, actually there is another problem that has not been touched, namely the problem of belief, principles of life, and faith in relation to education.  This problem is referred to as the “Theology of Education, ” a field that examines the values , spirit, and religious aspects as an integral part of education.